EFFECTIVENESS OF PUBLIC SPENDING IN BORDER REGION DEVELOPMENT: A SYSTEMATIC LITERATURE REVIEW ON BUDGET ALLOCATION AND DEVELOPMENT OUTCOMES - Marsela Diaz; Maria Christina Iman Kalis; M. Irfani Hendri (Universitas Tulungagung, 2026)
This study analyzes the effectiveness of public expenditure in border region development, with particular emphasis on the relationship between budget allocation and development outcomes. Using a Systematic Literature Review (SLR) guided by PRISMA 2020, this article synthesizes 27 selected studies published between 2016 and April 2026 from Scopus, Web of Science, ScienceDirect, and Google Scholar. The review shows that public expenditure contributes to economic growth, social welfare, and regional connectivity, particularly when directed to agriculture, education, infrastructure, health, and local economic development. However, its effectiveness is strongly conditioned by governance quality, institutional capacity, coordination across levels of government, fiscal transparency, and the fit between central planning and local needs. The findings also reveal that agriculture and education spending tend to produce more consistent positive outcomes than other spending categories because they directly strengthen local production capacity, human capital, and long-term welfare indicators. The article contributes analytically by positioning border regions as complex fiscal-policy spaces and by developing a synthesis framework that links budget allocation, priority sectors, implementation quality, local context, inequality, spillover effects, and development outcomes. The practical implication is that border development policy should move beyond budget absorption toward outcome-based, locally grounded, and evidence-based public spending strategies.